2021
DOI: 10.1155/2021/3838456
|View full text |Cite
|
Sign up to set email alerts
|

One Year Outcomes and Stability of a Novel Scleral Anchored Intraocular Lens

Abstract: Purpose. To assess one year results and stability of the implantation of a scleral anchored intraocular lens (IOL). Design. Interventional prospective case series. Methods. Sixty eyes of 60 patients affected by either aphakia or IOL dislocation were included in this study. Patients underwent vitrectomy, scleral fixation of the IOL, and, if present, dislocated IOL removal. Patients were evaluated preoperatively and at 1, 3, 6, and 12 months after surgery by best-corrected distance visual acuity (BCVA) assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Kumar et al found that the tilt angle after glued fixation was 3.2° and 2.9° in horizontal and vertical axes, respectively [ 8 ]. More recently, the study using a novel scleral anchored IOL revealed that the tilt angle was approximately 1° [ 25 ]. The mean tilt angle was 2.33° ± 1.36° in our series, which is lower than 7°, indicating a nonsignificant tilt and is comparable to that of routine cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al found that the tilt angle after glued fixation was 3.2° and 2.9° in horizontal and vertical axes, respectively [ 8 ]. More recently, the study using a novel scleral anchored IOL revealed that the tilt angle was approximately 1° [ 25 ]. The mean tilt angle was 2.33° ± 1.36° in our series, which is lower than 7°, indicating a nonsignificant tilt and is comparable to that of routine cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 82 studies were identi ed from the databases, 8 of which were duplicate and excluded 10,11,12,13,14,15,16,17 . Two independent researchers screened the titles and abstracts of the 74 studies, 52 of which were excluded, as they included individual case series (supplementary appendix).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In 2014, a sutureless scleral fixated IOL was designed by Carlo Carlevale and fabricated by Soleko, Italy. Following the introduction of the Carlevale IOL several authors have reported good surgical outcomes of its implantation (Abed et al., 2021; Barca et al., 2020; D'Agostino et al., 2021; Fiore et al., 2021; Gabai et al., 2021; Januschowski et al., 2021; Rossi et al., 2021; Rouhette et al., 2021; Sidiropoulos et al., 2022; Vaiano et al., 2021; Veronese et al., 2020).…”
Section: Introductionmentioning
confidence: 99%